In search of ancient mysteries - Warshofsky, Fred ([Australia] : Zerox films (distributor), 1974)
Evidence to support the theory that man on earth had his genesis somewhere in outer space is offered in this thought-provoking film. Filmed on locations throughout the world, some of the bizarre phenomena depicted include a complex astrological clock built in 50 B.C.
Title from container
Execvutive producer, Alan Landsburg, Laurence D. Saradove ; edited by Buck Speed
DVD format
Keywords: Civilization, ancient -- Extraterrestrial influences; Prehistoric peoples; History, Ancient